Hubungan antara bayi berat lahir rendah dengan kejadian refluks gastroesofagus di puskesmas Kecamatan Malalayang - Yuliantari, Kadek Rani; Manoppo, Jeanette I.Ch.; Lestari, Hesti (e-CliniC, 2016)
Abstract: Low birth weight (LBW) is one of the causes of infant mortality in Indonesia. One of the problems related to the maturity of digestive tract function in LBW infants is gastroesophageal reflux (GER) due to dysfunction of lower esophageal sphincter (LES). Gastroesophageal reflux is a physiological condition among infants under the age of 12 months. Albeit, it requires a special attention for LBW infants in order not to suffer from gastroesophageal reflux disease (GERD) which will affect growth and development. This study was aimed to determine the correlation between LBW and GER. This was an analytical observational study with a case-control design; each group consisted of 30 respondents. Respondents were mothers of children aged 0-2 years obtained by using purposive sampling at three primary health cares at Malalayang from September until November 2016. Infant gastroesophageal reflux questionnaire (I-GERQ) was used as instrument in this study. The result showed a significant correlation between LBW and GER groups (p=0.034) and OR 2.615. Conclusion: There was a significant correlation between LBW and GER. Low Birth Weight had a higher risk to suffer from GER. Woman are expected to give more attention for their health and nutrition during pregnancy to prevent LBW births.Keywords: BBLR, RGE, SEB, childrenÂ Abstrak: Bayi berat lahir rendah (BBLR) ialah salah satu penyebab kematian bayi di Indonesia karena kondisi tubuh yang belum stabil sehingga menimbulkan masalah pada sistem atau organ tubuh. Salah satu masalah terkait kematangan fungsi saluran cerna ialah refluks gastroesofagus (RGE) dimana terjadi disfungsi sfingter esofagus bawah (SEB). RGE merupakan kondisi fisiologik pada usia <12 bulan. Pada BBLR dibutuhkan perhatian khusus agar tidak berlanjut menjadi penyakit refluks gastroesofagus (PRGE) yang akan memengaruhi tumbuh kembang. Penelitian ini bertujuan untuk mengetahui hubungan antara BBLR dan kejadian RGE. Jenis penelitian ialah analitik observasional dengan studi kasus control, masing-masing terdiri dari 30 responden. Responden ialah ibu yang memiliki anak berusia 0-2 tahun diperoleh dengan metode purposive sampling pada tiga puskesmas di Kecamatan Malalayang bulan September hingga November 2016. Instrumen penelitian berdasarkan Infant-Gastroesophageal Reflux Questionnaire (I-GERQ). Hasil penelitian dari kelompok kasus dan kontrol menunjukkan terdapat hubungan bermakna antara BBLR dan kejadian RGE (p=0,034) dengan Odds Ratio 2,615. Simpulan: Terdapat hubungan bermakna antara BBLR dan kejadian RGE. BBLR memiliki risiko 2,6 kali mengalami RGE. Ibu hamil diharapkan lebih memperhatikan kesehatan dan asupan gizi untuk mencegah kelahiran BBLR. Kata kunci: BBLR, RGE, SEB, anak